Electromagnetic characterisation of conductive 3D‐Printable filaments for designing fully 3D‐Printed antennas. Issue 11 (27th July 2022) - Colella, Riccardo; Chietera, Francesco Paolo; Michel, Andrea; Muntoni, Giacomo; Casula, GiovanniAndrea; Montisci, Giorgio; Catarinucci, Luca
Abstract: Additive manufacturing (AM) 3D‐printing technology is increasingly bringing benefits even in electromagnetics, with interesting prospects of application. Apart from the use of additive manufacturing for realising dielectric components of suitably shaped antennas, the ambitious target is, undoubtedly, the fully 3D realisation of radiofrequency and microwave circuits as well as radiating structures, including, therefore, conductive parts. In this regard, 3D‐printable filaments with interesting conductive properties are being produced. However, their rigorous conductivity characterisation is still missing, making it difficult to estimate the real behaviour of the final 3D printed electromagnetic device. To fill this gap, the conductivity of one of the most interesting conductive filaments, named Electrifi, is first experimentally evaluated in a frequency range as large as 0.72–6 GHz, accounting also for its roughness. Then it has been validated by designing, realising, and testing three fully 3D‐printed antennas. Specifically, two bow‐tie antennas, operating at 2.8 and 4 GHz, respectively, and an ultrawideband antenna, borrowed from the existing literature, operating between 1 and 7 GHz. The good agreement between simulated and measured results demonstrates the reliability of the performed electrical conductivity characterisation, even in the design of efficient radiating structures entirely realised with thermoplastic materials with copper nanoparticle additives.